TANTANGAN INTEGRITAS DAN PROFESIONALITAS PENGAWAS PEMILU DI JAWA BARAT (ANALISIS PUTUSAN DKPP TERHADAP PENGAWAS PEMILU DI JAWA BARAT TAHUN 2020-2021) - Suhenty, Lolly (Jurnal Keadilan Pemilu, 2021)
Election Supervisory Agency (Bawaslu) is responsible for conducting elections in a democratic and dignied manner. Thus, the code of ethics becomes an integral and inherent value in the souls of election supervisors. In the local context, West Java is the area with the most Final Voter List (DPT), so the problem is more complex, including the number of complaints about alleged violations of the code of ethics against election supervisors. This paper uses a descriptive qualitative analysis method with a literature study through the study of Election Organizer Ethics Council (DKPP) decisions. As a result, it is proven that during the 2020–2021 period, there were 13 complaints of alleged violations of the code of ethics against the Election Supervisory Agency (Bawaslu) with 50 people competing, including 5 strong warnings, 23 warnings, and 22 rehabilitations. This demonstrates that there are two reasons, namely the existence of internal violations, both in terms of integrity and professionalism, and a lack of socialization and information on Bawaslu's work to the public. The challenges ahead are conducting strict recruitment, comprehensive guidance and technology, strengthening and consistency, maintaining integrity and professionalism, the priority of the prudence principle in speech, action, and decision making, and ensuring each division performs public relations work and publishes persuasively.